Microstructure Design of High-Entropy Alloys Through a Multistage Mechanical Alloying Strategy for Temperature-Stable Megahertz Electromagnetic Absorption - Liu, Xiaoji; Duan, Yuping; Guo, Yuan; Pang, Huifang; Li, Zerui; Sun, Xingyang; Wang, Tongmin (Nano-Micro Letters, 2022)
Developing megahertz (MHz) electromagnetic wave (EMW) absorption materials with broadband absorption, multi-temperature adaptability, and facile preparation method remains a challenge. Herein, nanocrystalline FeCoNiCr0.4Cu0.2 high-entropy alloy powders (HEAs) with both large aspect ratios and thin intergranular amorphous layers are constructed by a multistage mechanical alloying strategy, aiming to achieve excellent and temperature-stable permeability and EMW absorption. A single-phase face-centered cubic structure with good ductility and high crystallinity is obtained as wet milling precursors, via precisely controlling dry milling time. Then, HEAs are flattened to improve aspect ratios by synergistically regulating wet milling time. FeCoNiCr0.4Cu0.2 HEAs with dry milling 20 h and wet milling 5 h (D20) exhibit higher and more stable permeability because of larger aspect ratios and thinner intergranular amorphous layers. The maximum reflection loss (RL) of D20/SiO2 composites is greater than − 7 dB with 5 mm thickness, and EMW absorption bandwidth (RL < − 7 dB) can maintain between 523 and 600 MHz from − 50 to 150 °C. Furthermore, relying on the “cocktail effect” of HEAs, D20 sample also exhibits excellent corrosion resistance and high Curie temperature. This work provides a facile and tunable strategy to design MHz electromagnetic absorbers with temperature stability, broadband, and resistance to harsh environments. Highlights: 1 Nanocrystalline high-entropy alloy powders (HEAs) with the unprecedented combination of superior manufacturability, large aspect ratios, and thin intergranular amorphous layers are constructed via a multistage mechanical alloying strategy. 2 FeCoNiCr0.4Cu0.2 HEAs for 20 h of dry milling and 5 h of wet milling (D20) exhibit excellent corrosion resistance, high Curie temperature, and temperature-stable broadband megahertz electromagnetic wave absorption.